Effective Strategy for Kazakhstan Higher Education Institutions (HEIs) According to Best Practice in UK - Gulmira, Azretbergenova; Kumarbekuly, Sanat; Kelgembayeva, Bakytzhan; Kaldybay, Kainar (Journal of Ecohumanism, 2024)
This chapterexplores the process of strategy-making in higher education and the development of an effective strategy for universities. The author analyzes the strategies of 3 universities in Kazakhstan and a number of regulatory documents on strategy development. The strategies of leading universities in the UK such as the University of Oxford, and Falmouth University have been studied. The results of the study indicate the need to improve the strategy of universities in Kazakhstan and identifies external and internal factors impeding the implementation of strategies